How many times per week should a muscle be trained to maximize muscle hypertrophy? A systematic review and meta-analysis of studies examining the effects of resistance training frequency - Schoenfeld, B. J.; Grgic, J.; Krieger, J. (Journal of Sports Sciences, 2019)
Training frequency is considered an important variable in the hypertrophic response to regimented resistance exercise. The purpose of this paper was to conduct a systematic review and meta-analysis of experimental studies designed to investigate the effects of weekly training frequency on hypertrophic adaptations. Following a systematic search of PubMed/MEDLINE, Scoups, and SPORTDiscus databases, a total of 25 studies were deemed to meet inclusion criteria. Results showed no significant difference between higher and lower frequency on a volume-equated basis. Moreover, no significant differences were seen between frequencies of training across all categories when taking into account direct measures of growth, in those considered resistance-trained, and when segmenting into training for the upper body and lower body. Meta-regression analysis of non-volume-equated studies showed a significant effect favoring higher frequencies, although the overall difference in magnitude of effect between frequencies of 1 and 3+ days per week was modest. In conclusion, there is strong evidence that resistance training frequency does not significantly or meaningfully impact muscle hypertrophy when volume is equated. Thus, for a given training volume, individuals can choose a weekly frequency per muscle groups based on personal preference. Abstract from author